Pengaruh Electronic Word of Mouth dan Customer Experience terhadap Brand Trust Transmart Carrefour Kota Padang - Geny Syahdiany; Okki Trinanda (Jurnal Kajian Manajemen dan Wirausaha, 2019)
Purpose - The purpose of this study was to find out consumer responses to electronic word ofmouth, customer experience, and brand trust and influence partially and simultaneouslyelectronic word of mouth and customer experience on Transmart Carrefour brand trust inPadang City.Methodology - The data used in this study were obtained from questionnaires and directinterviews with related parties. The analysis technique used is multiple regression usinghypothesis testing, namely F test and T test.Finding - Regarding the causal model proposed, the data confirm the relationship set out in thehypothesis. It can therefore be stated that (1) Brand personality has a positive effect andsignificant to repurchase intention (2) Service quality has a positive effect and significant torepurchase intention and (3) Store Atmosphere has a positive effect and significant torepurchase intentionConclusion - Based on the T test, electronic word of mouth has a positive and not significanteffect on brand trust, customer experience has a positive and significant impact on brand trust.Keywords: Electronic Word of Mouth, Customer Experience, Brand TrustLatar Belakang